Theoretical Foundations of Professional Training of Future Teachers on the Basis of the Integration Approach (Texas Journal of Engineering and Technology, 2022)
Deficiencies in the process of professional-pedagogical and methodical training of future teachers of higher education institutions, problems and methods of their elimination, as well as issues of thinking ability, academic motivation, the ability to work in a team in network projects, and the impact of interdisciplinary communication on the quality of students' knowledge and skills illuminated